2016
DOI: 10.1111/1745-9125.12114
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Arrest for College Enrollment: An Analysis of Long‐term Effects and Mediating Mechanisms*

Abstract: This study draws on labeling theory and education research on the steps to college enrollment to examine 1) whether and for how long arrest reduces the likelihood that high‐school graduates will enroll in postsecondary education and 2) whether any observed relationships are mediated by key steps in the college enrollment process. With 17 years of data from the National Longitudinal Survey of Youth 1997 (NLSY97) and propensity score matching, we derived matched samples of arrested and nonarrested but equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 61 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…However, the stigma of police arrest did not exert a significant influence on two-year college enrollment because of the relatively loose admission requirements. Similarly, findings from the work of Widdowson, Siennick, and Hay (2016) showed that arrest exerts adverse influences on four-year college attendance but not on two-year college enrollment. Further, the cumulative influence of experiencing juvenile arrest can also impact college graduation.…”
Section: Cumulative Influences Of Labeling: Subsequent Delinquency Anmentioning
confidence: 88%
“…However, the stigma of police arrest did not exert a significant influence on two-year college enrollment because of the relatively loose admission requirements. Similarly, findings from the work of Widdowson, Siennick, and Hay (2016) showed that arrest exerts adverse influences on four-year college attendance but not on two-year college enrollment. Further, the cumulative influence of experiencing juvenile arrest can also impact college graduation.…”
Section: Cumulative Influences Of Labeling: Subsequent Delinquency Anmentioning
confidence: 88%
“…Life‐course theory demonstrates that both criminal justice contact and exclusion from economic opportunities concentrate during the transition to adulthood (Harding & Harris, 2020; Sampson & Laub, 1997; Widdowson et al., 2016). Economic attainment is cumulative across the life course, with earlier experiences in education and work shaping later economic opportunities (Lyons & Pettit, 2011).…”
mentioning
confidence: 99%
“…The bandwidth of .03 is consistent with that found in prior criminological research (e.g.,Widdowson, Siennick, & Hay, 2016), and it is slightly more conservative than bandwidths .05 or .06, which are commonly used with kernel matching (see, e.g.,Cui, Gordon, Ueno, & Fincham, 2013;Turney, 2017;Wiley, Slocum, & Esbensen, 2013).…”
mentioning
confidence: 99%